A maternity priority algorithm for emergency obstetric admissions. (16th November 2010) - Samangaya, RA; Whitworth, MK; Mason, J; Brockbank, A; Gillham, JC
Abstract : Introduction: Obstetric triage departments have been developed for pregnant women presenting to obstetric services with problems ranging from the trivial to potentially life threatening. There is a need to develop systems to prioritise these women appropriately. Methods: A maternity priority algorithm was devised based on well established A&E systems. The algorithm divides women into Red, Amber, Yellow or Green categories, and stipulates time guidelines for midwifery or medical review. A pilot survey of the algorithm was conducted over 1 month to determine; proportions in each category; appropriateness of each categorisation; ease of application. Results: There were 571 admissions. Nine (1.6%) cases were Red, 15 (2.6%) were Amber, 67 (11.4%) were Yellow and 472 (82.7%) were Green. Eight cases were not classified. 23 (4%) women were assigned to a higher category than appropriate; 23 (4%) women were under classified who all presented with reduced fetal movements. Allocated Red cases were seen immediately, as stipulated, in 78% of cases with remaining cases seen within 60 min. 60% of allocated Amber cases were seen within the recommended 15 min, with remaining cases seen within 1 h 46 min. 80.6% of allocated Yellow cases were seen within the recommended 45 min, with remaining cases seen within 1 h 40 min. Conclusions: While the majority of obstetric admissions are in the lowest priority category, the algorithm has proved relatively straightforward to apply and has good specificity. Further training about utilising the maternity priority algorithm and emphasis about timings is required.